2016
DOI: 10.1016/j.matdes.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of process capabilities in electrically-assisted double sided incremental forming

Abstract: Article available under the terms of the CC-BY-NC-ND licence (https://creativecommons.org/licenses/by-nc-nd/4.0/) eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…A master-slave tool layout for double-side incremental forming (DSIF) combined with electrically assisted heating was presented in [26]. Good results were reported in processing lightweight materials (AZ31B magnesium alloy) with regards to surface quality and maximum wall angle for truncated cone parts and a new type of hybrid toolpath lead to better geometric accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…A master-slave tool layout for double-side incremental forming (DSIF) combined with electrically assisted heating was presented in [26]. Good results were reported in processing lightweight materials (AZ31B magnesium alloy) with regards to surface quality and maximum wall angle for truncated cone parts and a new type of hybrid toolpath lead to better geometric accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…In ISF, the periphery of the sheet metal is clamped, while the material is locally deformed by one, i.e., Single Point Incremental Forming (SPIF), or more stylus tools that move along pre-defined toolpaths. Therefore, because of their dieless nature and high flexibility, these techniques are most suitable when low-volume customized sheet metal parts, as the case of biomedical implants, have to be manufactured [3].…”
Section: Introductionmentioning
confidence: 99%
“…One challenge in all the above incremental forming techniques is forming workpieces made of lightweight but difficult-to-form materials [3], such as Ti6Al4V. Because of its limited formability at room temperature [9], a possible solution to form Ti6Al4V sheets using ISF processes is to increase the forming temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In order to drive the model to predict the observed stress drop, the bulk temperature of the specimen exceeds experiment, while the dislocation density and grain boundary electrical resistivity exceed published values, thereby suggesting that microscale heterogeneous heating theory is not the full explanation for the transient electroplastic effect. A new theory for explaining the electroplastic effect based on dissolution of bonds is proposed called the Electron Stagnation Theory.The effect of electricity on metals during deformation, known as the electroplastic effect, can be utilized to reduce forming loads, springback, and flow stress while increasing ductility during various forming processes [1][2][3][4][5][6][7]. A review of the impact of electricity on various manufacturing processes is reported in Ref.…”
mentioning
confidence: 99%
“…The effect of electricity on metals during deformation, known as the electroplastic effect, can be utilized to reduce forming loads, springback, and flow stress while increasing ductility during various forming processes [1][2][3][4][5][6][7]. A review of the impact of electricity on various manufacturing processes is reported in Ref.…”
mentioning
confidence: 99%